Ethiopian Higher Education Expansion and Persisting Challenges: A Systematic Review - Oliso, Zelalem Zekarias (Unib Press, 2023)
Quality higher education plays a significant role in socio-economic development of a nation. Education service quality is one of the important parameters to measure the quality of higher education. The main purpose of this study was conducted to examine the persisting challenges in Ethiopian higher education. To this end, a qualitative research approach was followed. The data for the study were collected via document analysis, focus group discussions and interviews. A total of 89 research papers written on the Ethiopian higher education expansion and its quality was thoroughly reviewed. During the reviewing process, various government policy documents, peer reviewed articles, PhD dissertations, and empirical studies were consulted. The findings of the study revealed that even though different quality improvement programmes have been established to control the quality of Ethiopian higher education, those efforts brought low impact on the country’s higher education quality. The shortage of experienced teachers, insufficient supplies of academic resources such as Information Communication Technology [ICT] infrastructure, library facilities, laboratory and workshop equipment, poor dormitory services, lack of adequate classrooms are still persisting challenges of most Ethiopian higher education. It was, therefore, concluded that most Ethiopian higher education institutions provide poor service delivery to students. Based on these findings and conclusions, recommendations were forwarded.